The Effect of Work Motivation, Work Discipline, and Work Environment on Employee Performance at the Medan District Court - Devina Giovanny; Selvina Zai; Kristi Endah Ndilosa Ginting; Mella Yunita (SEAN Institute, 2026)
This study aims to analyze the influence of work motivation, work discipline, and work environment on employee performance at the Medan District Court. Employee performance is an important aspect in public institutions because it determines the effectiveness of administrative services, work completion, and institutional accountability. This research uses a quantitative approach with an associative research design. Data were collected through questionnaires distributed to employees of the Medan District Court. The data were analyzed using SPSS through validity and reliability tests, classical assumption tests, multiple linear regression analysis, partial tests, simultaneous tests, and coefficient of determination analysis. The results show that work motivation has a positive and significant effect on employee performance. Work discipline also has a positive and significant effect on employee performance, indicating that employee compliance with rules and work procedures contributes to better performance. In addition, the work environment has a positive and significant effect on employee performance and becomes the most dominant factor in this study. Simultaneously, work motivation, work discipline, and work environment have a significant effect on employee performance. These findings indicate that improving employee performance at the Medan District Court requires stronger motivation, consistent work discipline, and a more supportive work environment.